Rituximab in patients with acute ST-elevation myocardial infarction: an experimental medicine safety study. Issue 3 (30th March 2021) - Zhao, Tian X; Aetesam-Ur-Rahman, Muhammad; Sage, Andrew P; Victor, Saji; Kurian, Rincy; Fielding, Sarah; Ait-Oufella, Hafid; Chiu, Yi-Da; Binder, Christoph J; Mckie, Mikel; Hoole, Stephen P; Mallat, Ziad
Abstract: Aims: In pre-clinical models of acute myocardial infarction (MI), mature B cells mobilize inflammatory monocytes into the heart, leading to increased infarct size and deterioration of cardiac function, whilst anti-CD20 antibody-mediated depletion of B cells limits myocardial injury and improves cardiac function. Rituximab is a monoclonal anti-CD20 antibody targeted against human B cells. However, its use in cardiovascular disease is untested and is currently contraindicated. Therefore, we assessed the safety, feasibility, and pharmacodynamic effect of rituximab given to patients with acute ST-elevation MI (STEMI). Methods and results: Rituximab in patients with acute ST-elevation myocardial infarction (RITA-MI) was a prospective, open-label, dose-escalation, single-arm, phase 1/2a clinical trial, which tested rituximab administered as a single intravenous dose in patients with STEMI within 48 h of symptom onset. Four escalating doses (200, 500, 700, and 1000 mg) were used. The primary endpoint was safety, whilst secondary endpoints were changes in circulating immune cell subsets including B cells, and cardiac and inflammatory biomarkers. A total of 24 patients were dosed. Rituximab appeared well tolerated. Seven serious adverse events were reported, none of which were assessed as being related to the rituximab infusion. Rituximab caused a mean 96.3% (95% confidence interval 93.8–98.8%) depletion of circulating B cells within 30 min of starting the infusion. Maximal B-cell depletion was seen at Day 6, which was significantly lower than baseline for all doses ( P  < 0.001). B-cell repopulation at 6 months was dose-dependent, with modulation of returning B-cell subsets. Immunoglobulin (IgG, IgM, and IgA) levels were not affected during the 6 months of follow-up. Conclusions: A single infusion of rituximab appears safe when given in the acute STEMI setting and substantially alters circulating B-cell subsets. We provide important new insight into the feasibility and pharmacodynamics of rituximab in acute STEMI, which will inform further clinical translation of this potential therapy. Clinical trial registration: NCT03072199 at https://www.clinicaltrials.gov/ Graphical Abstract: